Breaking the Barriers and Building Empowerment: an Analysis on the Women Empowerment through the Self-Help Groups - Jisha TP; M. Sumathy (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study examines how self-help groups affect women's empowerment. Here, the study focuses on whether the group has any effect on women's empowerment. The study is analytical and makes use of both primary and secondary data. In this case, the researcher gathered primary data from the members of the self-help group of Palakkad district and secondary data from a variety of articles, magazines, and newspapers. Regression analysis, one-way anova, correlation coefficient, and independent t-test are the techniques employed in this research. The aforementioned studies, which were carried out in various parts of India, discovered that self-help groups affected women's empowerment. This study focuses on the various factors that contribute to women's empowerment through self-help groups. All of the prior research has generally discussed SHG membership and women's empowerment; however, this study focuses on a few key variables that lead to women's empowerment through the groups. The study discovered that women's empowerment is impacted by self-help groups. Taking part in the training program is one way to increase the ability to make decisions in the self-help group. Through the self-help group, the decision-making power within the group contributes to the empowerment of women. Women's empowerment is associated not only with their ability to make decisions within the group but also with their socioeconomic level and involvement in training programs.